Deliberate shot trajectories of highly skilled golfers: Associated changes and diversity in ground reaction forces - Prokopy, M. P.; Lee, S.; Perry, J. A.; Allin, L. J.; Hryvniak, D. J.; Weltman, A. L. (Translational Sports Medicine, 2018)
The approach shot is critical to golf performance, demanding precise control of distance, direction, and trajectory. Despite real-world importance, three-dimensional kinetic assessment of approach skill is lacking. We evaluated ground reaction forces (GRFs) of 6-iron approach shots of normal/stock (ST), high-draw (HD), and low-fade (LF) trajectories struck by 31 tournament professional and plus-handicap amateur golfers. A priori hypotheses were: HD would involve greater and earlier peak lead foot vertical GRF in the downswing (DS); and/or greater peak differences in DS anterior-posterior (AP) GRF, compared to ST and LF. Analysis of variance and post hoc testing supported our hypotheses. Peak lead foot vertical GRFs were 100.4%, 101.1%, and 103.8% of body-weight for ST, LF, and HD, respectively (P < 0.001). Peak vertical GRF occurred later in the DS when executing LF (P < 0.05). The peak difference in AP GRF was greater when executing HD (P < 0.001). Timing and magnitudes of GRF peaks varied widely between golfers. Even among accomplished golfers executing ST (their most reliable trajectory), standard deviations ranged from 18.7% to 72.7% of mean values. Between-golfer differences accounted for 89.9%-93.6% of the total variance. These data may encourage researchers and coaches to avoid rigid standards or generalized recommendations for GRF parameters as relates to performance.